2017
DOI: 10.3389/fpls.2017.01138
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Sphingolipid Enriched Plasma Membrane Regions and Long-Chain Base Composition during Mature-Fruit Abscission in Olive

Abstract: Sphingolipids, found in membranes of eukaryotic cells, have been demonstrated to carry out functions in various processes in plant cells. However, the roles of these lipids in fruit abscission remain to be determined in plants. Biochemical and fluorescence microscopy imaging approach has been adopted to investigate the accumulation and distribution of sphingolipids during mature-fruit abscission in olive (Olea europaea L. cv. Picual). Here, a lipid-content analysis in live protoplasts of the olive abscission z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Previously, we have reported that endocytosis, visualized by staining with fluorescent dye FM4-64, was strongly stimulated in AZ during olive ripe fruit abscission [ 50 ], which suggests that endomembrane trafficking likely modulates cell wall modifications during olive fruit abscission. Deposition changes in cell-wall material involve vesicle formation and transport, which is reflected by a high number of up-regulated genes found in ripe fruit and AZ tissues in olives ( Figure 6 , Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have reported that endocytosis, visualized by staining with fluorescent dye FM4-64, was strongly stimulated in AZ during olive ripe fruit abscission [ 50 ], which suggests that endomembrane trafficking likely modulates cell wall modifications during olive fruit abscission. Deposition changes in cell-wall material involve vesicle formation and transport, which is reflected by a high number of up-regulated genes found in ripe fruit and AZ tissues in olives ( Figure 6 , Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A pool of 100 mg fresh weight of samples was used for each measurement, and divided into three independent biological replicates. Sterols were quantified by gas chromatography–mass spectrometry as described in (Parra‐Lobato et al ). As an internal standard, 5‐alpha cholestane (Sigma‐Aldrich) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Purified cDNA (2 ng) was used as a template for qRT‐PCR. Quantitative RT‐PCR was performed and analyzed as described by Parra‐Lobato et al (). The qRT‐PCR assays were performed with gene‐specific primers.…”
Section: Methodsmentioning
confidence: 99%
“…Although sphingomyelin is not present as such in plants, the structure has the features of a complex sphingolipid. Plants have an enormous variety of these lipids and they show a physicochemical behavior expected for a complex sphingolipid, therefore, BD-SM molecules incorporate into the plasma-membrane and mixed with native sphingolipids ( Blachutzik et al, 2012 ; Parra-Lobato et al, 2017 ). Referring to information of the manufacturer, BD-SM features the same stereochemical conformation as biologically active sphingomyelins, despite the fluorescence labeling.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental work has clearly established that sphingolipids are essential to sustain the vegetative growth of Arabidopsis ( Dietrich et al, 2008 ) but also for adequate pollen development and competence ( Chen et al, 2008 ; Rennie et al, 2014 ). Recently, we reported the first evidence for the potential involvement of sphingolipids in abscission processes as well as an increase in the relative content of sphingolipids during mature-fruit abscission in live protoplasts from abscission zone cells ( Gil-Amado and Gomez-Jimenez, 2013 ; Parra-Lobato et al, 2017 ). However, information regarding their possible involvement in fleshy-fruit development and ripening, a plant-specific process, is still lacking.…”
Section: Introductionmentioning
confidence: 99%